Response to MacNeilage and Davis and to Oller - Whalen, D. H. (2011)
The article by MacNeilage and Davis in this issue, entitled “In Defense of the ‘Frames, then Content’ (FC) Perspective on Speech Acquisition: A Response to Two Critiques” appears to assume that the only alternative to segment-level control is oscillation specifically of the jaw; however, other articulators could be oscillated by infants as well. This allows the preferred CV combinations to emerge without positing a level of segmental control in babbling. Their response does not address our modeling work, which, rather similarly to Davis’s own modeling (Serkhane, Schwartz, Boë, Davis, & Matyear, 2007), shows little support for the Frame-then-Content (F/C) account. Our results show substantial support for the Articulatory Phonology (AP) one. A closer look at feeding in infants shows substantial control of the tongue and lips, casting further doubt on the foundation of the F/C account.